2008
DOI: 10.1016/j.jns.2007.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of utrophin gene worsens skeletal muscle inflammation and fibrosis in mdx mice

Abstract: To address whether mdx mice with haploinsufficiency of utrophin (mdx/utrn+/-) develop more severe skeletal muscle inflammation and fibrosis than mdx mice, to represent a better model for Duchenne muscular dystrophy (DMD), we performed qualitative and quantitative analysis of skeletal muscle inflammation and fibrosis in mdx and mdx/utrn+/- littermates. Inflammation was significantly worse in mdx/utrn+/- quadriceps at age 3 and 6 months and in mdx/utrn+/- diaphragm at age 3 but not 6 months. Fibrosis was more se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
1
16

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 16 publications
6
83
1
16
Order By: Relevance
“…Entretanto estes animais apresentam um fenótipo mais brando da DMD e após períodos de pico de inflamação, os músculos do mdx com exceção do músculo diafragma, voltam a apresentar sua função restaurada. Tal compensação funcional nestes animais tem sido atribuída a expressão de utrofina no sarcolema das células musculares de camundongos adultos, que atua restaurando proteínas do complexo distrofina, protegendo o fenótipo da distrofia muscular no camundongo mdx de forma dose-dependente (Zhou et al 2008, Huang et al 2011, Van Putten et al 2012.…”
Section: Introductionunclassified
“…Entretanto estes animais apresentam um fenótipo mais brando da DMD e após períodos de pico de inflamação, os músculos do mdx com exceção do músculo diafragma, voltam a apresentar sua função restaurada. Tal compensação funcional nestes animais tem sido atribuída a expressão de utrofina no sarcolema das células musculares de camundongos adultos, que atua restaurando proteínas do complexo distrofina, protegendo o fenótipo da distrofia muscular no camundongo mdx de forma dose-dependente (Zhou et al 2008, Huang et al 2011, Van Putten et al 2012.…”
Section: Introductionunclassified
“…Inflammation and fibrosis in both skeletal muscle and diaphragm are more severe than in the mdx mouse, but less than in the mdx/utrn -/-mouse. Their life span is significantly longer than that of mdx/utrn -/-mice (Zhou et al, 2008).…”
Section: Mouse Models For Dmdmentioning
confidence: 91%
“…However the dramatically reduced lifespan of these mice can hamper their experimental use [40]. In an attempt to circumvent this problem it was reported that haploinsufficiency of utrophin in the mdx;utrn +/-mouse worsens SM pathology compared to the mdx, whilst extending life expectancy compared to the mdx;utrn -/- [42,43].). Some groups are using the golden retriever (GRMD) dog model, however a major limitation is the dramatic variation in phenotype which is often observed even between littermates [44].…”
Section: Preclinical Models Of Dmdmentioning
confidence: 99%